EFFECTS OF ESG BEFORE AND DURING COVID-19 TO INDONESIA FIRM PERFORMANCE - Jeanice Jeanice; Sung Suk Kim (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
Today, seeing the progress of the world that continues to develop, the issues faced are also increasingly varied. According to data from the United Nations, the war between Russia and Ukraine has exacerbated the global cost of living crisis. Apart from this war, the Covid-19 pandemic also continues to be in the spotlight of global media around the world. These two things can be used as one of the reasons for the crisis that the world is currently facing. Companies with good ESG implementation will have keen knowledge of long-term strategic issues so that they can manage their long-term goals. For this reason, ESG performance is used as a benchmark for sustainable development in business decisions and in facing corporate crises. This research was conducted with the aim to find out how the effect of the application of ESG on company value and also in moderation during a crisis. This study uses a classic assumption test analysis with a sample of 71 companies in this study and the period 2008-2021 (14 years) with a total of 994 datas observed. The data used in this study were taken from the financial reports of companies listed on the IDX and the Bloomberg ESG Index for 2008-2021. The results showed that the ESG variable had a significant positive effect on ROE and PBV. Meanwhile, with moderation during the crisis, ESG has no significant effect on ROE and PBV.